Repair of tracheal epithelium by basal cells after chlorine-induced injury - Musah Sadiatu; Chen Jing; Hoyle Gary W (Respiratory Research, 2012)
Abstract Background Chlorine is a widely used toxic compound that is considered a chemical threat agent. Chlorine inhalation injures airway epithelial cells, leading to pulmonary abnormalities. Efficient repair of injured epithelium is necessary to restore normal lung structure and function. The objective of the current study was to characterize repair of the tracheal epithelium after acute chlorine injury. Methods C57BL/6 mice were exposed to chlorine and injected with 5-ethynyl-2′-deoxyuridine (EdU) to label proliferating cells prior to sacrifice and collection of tracheas on days 2, 4, 7, and 10 after exposure. Airway repair and restoration of a differentiated epithelium were examined by co-localization of EdU labeling with markers for the three major tracheal epithelial cell types [keratin 5 (K5) and keratin 14 (K14) for basal cells, Clara cell secretory protein (CCSP) for Clara cells, and acetylated tubulin (AcTub) for ciliated cells]. Morphometric analysis was used to measure proliferation and restoration of a pseudostratified epithelium. Results Epithelial repair was fastest and most extensive in proximal trachea compared with middle and distal trachea. In unexposed mice, cell proliferation was minimal, all basal cells expressed K5, and K14-expressing basal cells were absent from most sections. Chlorine exposure resulted in the sloughing of Clara and ciliated cells from the tracheal epithelium. Two to four days after chlorine exposure, cell proliferation occurred in K5- and K14-expressing basal cells, and the number of K14 cells was dramatically increased. In the period of peak cell proliferation, few if any ciliated or Clara cells were detected in repairing trachea. Expression of ciliated and Clara cell markers was detected at later times (days 7–10), but cell proliferation was not detected in areas in which these differentiated markers were re-expressed. Fibrotic lesions were observed at days 7–10 primarily in distal trachea. Conclusion The data are consistent with a model where surviving basal cells function as progenitor cells to repopulate the tracheal epithelium after chlorine injury. In areas with few remaining basal cells, repair is inefficient, leading to airway fibrosis. These studies establish a model for understanding regenerative processes in the respiratory epithelium useful for testing therapies for airway injury.